Functional Allium fistulosum Centromeres Comprise Arrays of a Long Satellite Repeat, Insertions of Retrotransposons and Chloroplast DNA - Kirov, Ilya; Odintsov, Sergey; Omarov, Murad; Gvaramiya, Sofya; Merkulov, Pavel; Dudnikov, Maxim; Ermolaev, Alexey; Van Laere, Katrijn; Soloviev, Alexander; Khrustaleva, Ludmila (Frontiers in Plant Science, 2020)
The centromere is a unique part of the chromosomes combining a conserved function with an extreme variability in its DNA sequence. Most of our knowledge about the functional centromere organization is obtained from species with small and medium genome/chromosome sizes while the progress in plants with big genomes and large chromosomes is lacking behind. Here, we studied the genomic organization of the functional centromere in Allium fistulosum and A. cepa, both species with a large genome (13Gb and 16Gb/1C, 2n=2x=16) and large-sized chromosomes. Using low-depth DNA sequencing for these two species and previously obtained CENH3 immunoprecipitation data we showed that the centromeres of both species possess long (1.2Kb) and high-copy tandem repeats, AfCen1K and AcCen1K. Our molecular cytogenetic and bioinformatics survey demonstrated that these repeats are partially similar but differ in chromosomal location, sequence structure and genomic organization. In addition, we could conclude that the repeats are transcribed and their RNAs are not polyadenylated. We also observed that the landscape of A. cepa and A. fistulosum centromeric regions is shaped by multiple insertions of retrotransposons and plastidic DNA. Finally, we carried out detailed comparative satellitome analysis of A. cepa and A. fistulosum genomes and identified a new chromosome- and A. cepa-specific tandem repeat, TR2CL137, located in the centromeric region. Our results shed light on the Allium centromere organization and provide unique data for future application in Allium genome annotation.